Generation of two Betacellulin CRISPR-Cas9 knockout hiPSC lines to study the affected EGF system paradigm in schizophrenia - Agustin Cota-Coronado; Murray Manning; Dong-Hyung Kim; Joohyung Lee; Andrew Gibbons; Joseph Rosenbluh; Rachel A. Hill; Suresh Sundram (Stem Cell Research)
Several members of the epidermal growth factor (EGF) family have been implicated in the biology of schizophrenia (Ketharanathan et al., 2024). The EGF-related ligand, Betacellulin (BTC), plays an important role in the proliferation and differentiation of neural stem cells and our group found markedly reduced BTC levels in patients with schizophrenia. Nevertheless, the interplay of affected BTC and its participation in neural specification and neurodevelopment remains elusive. We generated Knockout (KO) − BTC clones from an existing hiPSC line through CRISPR/Cas9-mediated modification. Furthermore, we validated BTC-KO through genotyping/sequencing, FACS and Western Blot. Finally, we demonstrated trilineage differentiation potential in vitro.